MODULATION TECHNIQUE IN TRANSLATING HEDGING DEVICES INTO INDONESIAN IN SHERLOCK HOLMES BY SIR ARTHUR CONAN DOYLE - Sujana, Sujana; Nababan, M. R.; Santosa, Riyadi; Wiratno, Tri (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Hedging devices are often used to express opinion rather than a fact of a proposition. Hedging devices are also expressing speaker uncertainty. What will happen when hedging devices are translated into the target language? Based on that question writer try to find out on how hedging devices are translated into target language using modulation technique. By using modulation technique, translator tries to understand the meaning of the hedging devices with different point of view. This study used qualitative methods in analyzing the data. The source data of this study is a novel written by Sir Arthur Conan Doyle, entitled Sherlock Holmes and its translation. Hedging devices found in this study were 96 data. Those data were translated using modulation technique. 96 data were divided into four such as, adaptors 66 data, rounders 6 data, plausibility shields 17 data and attribution shields 7 data. By using modulation technique translator translate those hedging devices with different hedging devices in the target language, but the function of the hedging devices are similar with the hedging devices of the source language.